2021
DOI: 10.1007/s40489-021-00260-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Studies of Reception of Facial Communication in Autism Spectrum Disorder and Schizophrenia

Abstract: Autism spectrum disorder (ASD) and schizophrenia spectrum disorders (SZ) are both characterized by difficulty with social cognition. Likewise, social brain activity is atypical in both disorders and indicates atypical reception of facial communicationa key area in the Research Domain Criteria framework for identifying common biological underpinnings of psychiatric disorders. To identify areas of overlap and dissociation between ASD and SZ, this paper reviews studies of electrophysiological (EEG) response to fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 181 publications
(430 reference statements)
0
1
0
Order By: Relevance
“…A meta-analysis proved that the N170 is sensitive to facial expressions [ 13 ]. Multiple studies have shown that longer latency periods are associated with face-processing difficulties in ASD [ 30 , 37 , 38 , 39 ]. Previous ERP studies investigating face processing have demonstrated that individuals with ASD across different age groups, including children, adolescents, and adults, exhibit delayed N170 latencies compared to TD individuals [ 36 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis proved that the N170 is sensitive to facial expressions [ 13 ]. Multiple studies have shown that longer latency periods are associated with face-processing difficulties in ASD [ 30 , 37 , 38 , 39 ]. Previous ERP studies investigating face processing have demonstrated that individuals with ASD across different age groups, including children, adolescents, and adults, exhibit delayed N170 latencies compared to TD individuals [ 36 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%